Dielectrophoretic choking phenomenon in a converging-diverging microchannel - Ai, Ye (American Institute of Physics, 2010)
Experiments show that particles smaller than the throat size of converging-diverging microchannels can sometimes be trapped near the throat. This critical phenomenon is associated with the negative dc dielectrophoresis arising from nonuniform electric fields in the microchannels. A finite-element model, accounting for the particle-fluid-electric field interactions, is employed to investigate the conditions for this dielectrophoretic (DEP) choking in a converging-diverging microchannel for the first time. It is shown quantitatively that the DEP choking occurs for high nonuniformity of electric fields, high ratio of particle size to throat size, and high ratio of particle’s zeta potential to that of microchannel.